Treatment strategies and outcomes in diffuse large B-cell lymphoma among 1011 patients aged 75 years or older: A Danish population-based cohort study. (August 2018) - Juul, Maja Bech; Jensen, Pernille Hammershoej; Engberg, Henriette; Wehberg, Sonja; Dessau-Arp, Andriette; Haziri, Donika; Kristensen, Helene Bjoerg; Baech, Joachim; Schurmann, Lene; Clausen, Michael Roost; Valentin, Rebecca; Knudsen, Lene Meldgaard; et al.
Abstract: Background: Optimal treatment strategy for the oldest patients with diffuse large B-cell lymphoma (DLBCL) remains controversial, as this group often is precluded from clinical trials, and population-based studies are limited. Methods: All Danish DLBCL-patients ≥75 years diagnosed from 2003 to 2012 were identified, using the Danish National Lymphoma Registry (LYFO). Information regarding baseline characteristics, treatment, comorbidities and outcomes was retrieved from LYFO, the Danish National health registries and medical records. Patients were stratified by age (75–79; 80–84 and 85 + years), comorbidity score and treatment modality (standard treatment [R-CHOP/CHOP-like], less intensive regimens or palliative treatment). Findings: A total of 1011 patients were included. Standard treatment was initiated in 64%, ranging from 83% among patients aged 75–79 years to 32% among patient aged 85 + years. With standard treatment, median overall survival (OS) estimates were 4·6, 2·6, and 1·9 years for the age groups 75–79, 80–84 and 85+ years. Among patient aged 75–79 and 80–84 years, OS was superior with standard treatment, although high comorbidity scores attenuated this association. Among patients aged 85+ years, survival was not influenced by treatment intensity. Patients ≥80 years had similar OS regardless of intended (R-)CHOP dosing, whereas patients of 75–79 years scheduled for full dose had higher OS. Standard treatment was not associated with increased hospitalisation. Interpretation: Standard treatment is feasible with good outcomes in a large proportion of elderly DLBCL-patients. Planned dose reduction in patients aged ≥80 years had no negative impact on OS. Highlights: Outside clinical trials, R-CHOP provides durable remissions among old DLBCL-patients. Age ≥85 years or age ≥80 years with high comorbidity score impairs outcome. No excess hospitalisation with R-CHOP. No adverse impact on OS with planned dose reduction in patients above 80 years. Less intensive regimens may be preferred among the oldest and most comorbid patients.